Pengaruh Ketinggian Dan Panjang Saluran Air Laut Terhadap Daya Yang Dihasilkan Pada Prototype Tidal Barrage - Sakti, Bima; Alham, Nur Rani; Fajri, Ahmad Nur; Ma’rif, Ilham Rizal (Universitas Hang Tuah, 2020)
The need for electricity in Indonesia is very important considering the limited resources and the lack of manpower, making Indonesia desperately need to increase electricity generation. One source of energy that can be converted into electrical energy is tidal barrage using the tidal barrage method. The application of this energy is still very small in Indonesia but there are a number of areas that have the potential to be implemented by the power plant. Tidal power plants that utilize the potential energy contained in the differences in tides and tides of sea water by trapping water in dams and then moving water turbines and when the water turbine is connected to a generator can produce electrical energy. Related to how the output of the generated power can it is known by looking at what height the water level drives the turbine. This type of power plant is environmentally friendly because it does not damage the natural ecosystem and the dam can be used for various activities.